Inovasi Pembelajaran Berbasis Media Qr Code Dalam Meningkatkan Motivasi Belajar Matematika Di SD Negeri Birowo 02 Binangun Blitar - Khoirudin, Mohammad; Sukoriyanto, Sukoriyanto; Dewi, Radeni Sukma Indra (Universitas Nahdlatul Ulama Blitar, 2024)
The aim of this research is to determine learning innovation and increase student motivation in mathematics lessons based on the PBL method and QR-Code media. The method used is qualitative with a case study type. Data was obtained through interviews, observation and documentation. Data analysis uses three simultaneous steps, namely data condensation, verification and presentation. The research results state that learning innovations based on QR-Code media can speed up understanding in the learning process, clarify the presentation of material considering that it is displayed using gadgets owned by students, learning time can be conditioned while eliminating students' boredom, and most importantly increase students' learning motivation in mathematics subjects. Student motivation is slowly being built using QR-Code media, making learning more effective, active and fun. The effectiveness of learning is influenced by the learning methods and media used. The two are interrelated, where the choice of a particular method will influence the type of media that will be used. In the sense that there must be a match between the two to realize the goals of mathematics learning.